Registration of 'HighWest' meadow bromegrass. Issue 2 (6th April 2022) - Jensen, Kevin B.; Winter, Damon; Bushman, B. Shaun; Robbins, Matthew; Getz, Megan; Waldron, Blair L.
Abstract: The USDA‐ARS announces the release of the meadow bromegrass [ Bromus biebersteinii Roem. & Schult. (excluded)] cultivar 'HighWest' (Reg. no. CV‐25, PI 698169) for use on irrigated and semi‐irrigated pastures as a rapidly establishing forage grass with excellent dry matter yield (DMY) on sites receiving 350 mm of either annual precipitation or irrigation. Selection emphasis in HighWest meadow bromegrass was on crude protein (CP), DMY regrowth, quality, and seedling emergence from a deep planting depth under irrigation. HighWest has been evaluated in Utah comparing it to meadow bromegrass cultivars 'Cache', 'Arsenal', 'Regar', 'Admiral', and 'Armada'. Genotyping by sequencing demonstrated that HighWest is significantly different genetically from Cache ( P < .043), Arsenal ( P < .003), Regar ( P < .040), Admiral ( P < .001), and Armada ( P < .028) and grouped closest to Cache and Arsenal, consistent with its breeding pedigree. HighWest had greater ( P < .05) percentage seedling emergence frequency at Millville, UT, compared with Arsenal, Regar, Armada, and Admiral. Based on a selection index that combined percentage seedling emergence frequency, DMY, and CP values, HighWest had a greater index value at 2.8 compared with Cache (1.7), Arsenal (−0.6), Regar (−3.2), Armada (−1.5), and Admiral (−1.0). Dry matter yield regardless of harvest date was similar to Cache, Arsenal, Regar, Admiral, and Armada. Forage regrowth of HighWest had CP values 6% greater than Cache. Water‐soluble carbohydrates were 22% greater in HighWest (87.0 g kg −1 ) than Cache. HighWest provides ranchers with additional plant material that maintains DMY and improves forage regrowth quality over the cultivar Cache. Core Ideas: HighWest is a new meadow bromegrass cultivar for use under irrigation and semi‐irrigation. HighWest has greater seedling emergence and vigor than most meadow brome cultivars. Based on combined seedling vigor, dry matter yield, and crude protein values, HighWest had greater index values. Water‐soluble carbohydrates values were always equal to, and sometimes greater than, other cultivars. Genetically, HighWest is distinct from other meadow brome cultivars in this study.